Development and Method Validation of HPLC Method as an Key Method in the Analysis of Olopatadine HCl - Theodorus Rexa Handoyo; Violetta Djohansah; Windy Annisa Arbah (Jurnal FARMASIMED (JFM), 2025)
Olopatadine hydrochloride (HCl) is a widely used second-generation antihistamine, and its accurate quantification is critical to ensure product quality and therapeutic efficacy. Reliable analytical methods are therefore essential for regulatory compliance and routine quality control. This study aimed to develop and validate a simple and robust high-performance liquid chromatography (HPLC) method for the determination of olopatadine HCl in pharmaceutical samples. The method was validated in accordance with USP <1225>, AOAC, and ICH Q2(R1) guidelines, with evaluation of key parameters including linearity, accuracy, precision, selectivity, sensitivity, and system suitability. The validation outcomes confirmed that the method provided strong linearity across the tested range, acceptable recovery values, excellent repeatability, and sufficient sensitivity for low-level detection. Overall, the developed HPLC method proved to be accurate, precise, selective, and reliable. Its simplicity and cost-effectiveness make it particularly suitable for routine quality control of olopatadine HCl in research and pharmaceutical industry laboratories.